Obsessive Compulsive Symptoms Are Associated With Heightened Avoidance of Low-Probability, High-Aversion Threats: A Preliminary Test of the Improbable-Catastrophe Hypothesis. (May 2022) - Hunt, Christopher; Degeneffe, Nikki; Bixby, Johanna; Lissek, Shmuel
Although symptoms of obsessive compulsive disorder (OCD) may vary markedly, they often involve a fear of consequences that are both catastrophic and highly improbable (e.g., contracting HIV from a doorknob). Accordingly, a heightened sensitivity to what we refer to as improbable catastrophes may represent an underlying feature of OCD, yet this possibility awaits experimental validation. To fill this gap, 78 undergraduates with wide-ranging levels of OCD symptom severity completed a fear-conditioning paradigm designed to elicit varying degrees of perceived threat probability/aversiveness to test whether OCD symptoms predict heightened reactivity to unlikely, high-aversion threats. Consistent with predictions, participants with higher OCD symptoms were more avoidant of low-probability, high-aversion threats and also exhibited greater threat expectancy and physiological reactivity to more improbable threats in general. These findings implicate excessive avoidance of improbable catastrophes and heightened reactivity to unlikely threats more generally as underlying features of OCD.